Dye activation of heterogeneous Copper(II)-Species for visible light driven hydrogen generation. (1st November 2019) - Kreft, Stefanie; Radnik, Jörg; Rabeah, Jabor; Agostini, Giovanni; Pohl, Marga-Martina; Gericke, Eike; Hoell, Armin; Beller, Matthias; Junge, Henrik; Wohlrab, Sebastian
Abstract: Heterogeneous Cu catalysts are widely used in photocatalytic hydrogen generation. The typical working mode includes the transfer of photo-induced charges from a semiconductor to CuO which itself is reduced to Cu2 O to initiate the catalytic cycle. In this contribution a photosensitizer (dye), excited by visible light absorption, was used to transfer an electron to the CuO which after reduction catalyzes the water reduction to hydrogen. Several copper(II)-catalysts on high surface silica were prepared by impregnation or precipitation and applied in photocatalytic water reduction. The best catalyst CuO(Cl0.1)/SiO2, synthesized via incipient wetness impregnation of CuCl2 in MCM-41 and a following precipitation with NaOH, achieved a 6 times higher activity (1702 mmol h −1  g −1 ) compared to a previously investigated copper system (280 mmol h −1  g −1 for CuI) under the same reaction conditions. All materials were fully characterized by XRD, TEM and N2 sorption and further by magnetic resonance and X-ray methods EPR, ASAXS and XAS. In situ measurements evidenced a reduction of the initial Cu(II)-species, which confirms the (proposed) photocatalytic mechanism. Graphical abstract: Image 1 Highlights: Cu-heterogenization of the Ir/Cu based photocatalytic water splitting system. Cu(II)-species were supported on SiO2 and investigated via TEM, ASAXS and XAS. Electrons from Ir-dye are transferred to Cu which then generates H2 after reduction. In situ EPR and XANES verified the proposed mechanism. A 6 times higher activity compared to the best homogeneous copper system was achieved.